2006
DOI: 10.1634/stemcells.2006-0125
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Novel Rhesus Monkey Embryonic Stem Cell Lines

Abstract: ESCs are important as research subjects since the mechanisms underlying cellular differentiation, expansion, and self-renewal can be studied along with differentiated tissue development and regeneration in vitro. Furthermore, human ESCs hold promise for cell and tissue replacement approaches to treating human diseases. The rhesus monkey is a clinically relevant primate model that will likely be required to bring these clinical applications to fruition. Monkey ESCs share a number of properties with human ESCs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(132 citation statements)
references
References 39 publications
3
128
1
Order By: Relevance
“…Here, ESC derivation efficiency improved with an increase in blastocyst age from day 6 (14%) to day 9 (41%) and use of DMEM/F12 also showed an increase in ESC isolation efficiency (39%) compared to DMEM (12%) along with a faster growth rate (Mitalipov et al 2006). Similar to mESCs and hESCs, these non-human primate ESC lines express pluripotency genes which can be passaged over long periods with normal karyotype, form teratomas, and like mESCs, they are able to form chimeras (Mitalipov et al 2006). Isolation of porcine ESCs from early blastocysts (day 7-9) was reported following mESC derivation (Anderson et al 1994).…”
Section: Embryonic Stem Cells In Domestic Animalsmentioning
confidence: 81%
See 1 more Smart Citation
“…Here, ESC derivation efficiency improved with an increase in blastocyst age from day 6 (14%) to day 9 (41%) and use of DMEM/F12 also showed an increase in ESC isolation efficiency (39%) compared to DMEM (12%) along with a faster growth rate (Mitalipov et al 2006). Similar to mESCs and hESCs, these non-human primate ESC lines express pluripotency genes which can be passaged over long periods with normal karyotype, form teratomas, and like mESCs, they are able to form chimeras (Mitalipov et al 2006). Isolation of porcine ESCs from early blastocysts (day 7-9) was reported following mESC derivation (Anderson et al 1994).…”
Section: Embryonic Stem Cells In Domestic Animalsmentioning
confidence: 81%
“…This pioneering achievement paved the way to isolate ESCs in various other animals such as in chicken, hamsters, cows, buffaloes, pigs, goats, horses, sheep, rabbits, dogs, cats and monkeys (rhesus and cynomolgus) (Doetschman et al 1988;Cherny et al 1994;Pain et al 1996;Li et al 2006;Mitalipov et al 2006;Brevini et al 2007;Wang et al 2007;Schneider et al 2008;Yu et al 2008;Pant & Keefer 2009;Sanna et al 2010;Kumar De et al 2011). …”
Section: Embryonic Stem Cells In Domestic Animalsmentioning
confidence: 99%
“…The three unstable ESC lines (ORMES-1, -2, and -5) showed, even at low passages, structural abnormalities, such as translocations (t(11;16) and t(5;19) with der (18) t(1;18)), or invertions (inv (1)). It has been hypothesized that the collagenase-based dissociation technique, used for ORMES-1, -2, and -5, may have contributed to the onset of karyotypic abnormalities in these cell lines (Mitalipov et al, 2006). Mouse Unexpectedly, an accurate literature search showed that only a few papers described the genomic variation of mESCs during a long period of culture.…”
Section: Non-human Primatesmentioning
confidence: 99%
“…A potentially important difference between the human and rhesus ESCs is the fact that the rhesus ESCs derived in the Thomson laboratory were from in vivo produced blastocysts, whereas all hESCs have been derived from IVF-produced embryos. Further studies are needed with rhesus ESCs derived from IVF-produced embryos (Mitalipov et al 2006) or from rhesus nuclear transfer-generated blastocysts (Byrne et al 2007). …”
Section: Future Directions: Further Studies With Rhesus Escmentioning
confidence: 99%